Steaming duration-dependent effects on the in vivo distribution, anti-fatigue activity, and gut microbiota modulation of Polygonatum cyrtonema Hua polysaccharides - Lin, Shengrong; Wang, Yanling; Wu, Weijing; Huang, Jiaqi; Cai, Xinqi (Frontiers in Pharmacology, 2026)
BackgroundPolygonatum cyrtonema Hua is a traditional medicinal plant widely used for its anti-fatigue properties, with its polysaccharides (PCPs) believed to play a key role in these effects. Steaming, a necessary step before consumption, can alter the structure of PCPs. However, the impact of steaming-induced structural changes on their anti-fatigue activity remains unexplored. This study aims to investigate how different steaming durations affect the distribution, anti-fatigue activity, and modulation of gut microbiota by PCPs.MethodsP. cyrtonema rhizomes were steamed for 0, 4, 8, and 12 h, and the polysaccharides were extracted. In vivo distribution was evaluated by conjugating PCPs with fluorescein isothiocyanate (FITC) for optical imaging. Anti-fatigue effects were assessed via exhaustive swimming tests, and serum biochemical markers were analyzed. Short-chain fatty acids (SCFAs) in feces were quantified by gas chromatography, while gut microbiota composition was analyzed using 16S rRNA sequencing. Network pharmacology analysis was performed to identify the biological targets of PCPs and their role in fatigue.ResultsThe results showed that all four PCPs exhibited poor systemic absorption but prolonged colonic retention, suggesting that interactions with the gut microbiota are central to their biological effects. While all PCPs improved exercise endurance, the 12-h steaming treatment notably decreased biochemical markers such as lactate and lactate dehydrogenase levels. Microbiota analysis revealed increased gut microbial α-diversity and short-chain fatty acids (SCFAs), with the 4-h and 8-h steaming groups showing the highest SCFA levels. β-diversity analysis indicated distinct microbial shifts, particularly between raw and steamed samples. Network pharmacology analysis highlighted differences in the mechanisms between raw and steamed PCPs, identifying key biological targets related to the anti-fatigue effects. The analysis suggested that the duration of steaming affects the biological activity of PCPs by modulating key metabolic pathways and targets involved in fatigue.ConclusionThese findings suggest that steaming-induced structural changes affect function and that the duration of steaming plays a crucial role in preserving the anti-fatigue effects of P. cyrtonema rhizomes. The results provide valuable insights for optimizing the steaming process to enhance the anti-fatigue potential of P. cyrtonema.